1999
DOI: 10.3171/foc.1999.6.4.17
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendoscopic approach to tectal tumors: a consecutive series

Abstract: The authors report a consecutive series of 10 patients who presented with signs and symptoms caused by tectal tumors. Clinical findings, radiographic features, neuroendoscopic management strategies, and histological findings are reported and discussed. Since January 1990, 11 neuroendoscopic procedures were performed in 10 patients who harbored tectal tumors. The patients were followed for an average of 5 years (range 2 months to 12 years), and a retrospective study was conducted in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
(27 reference statements)
1
10
0
1
Order By: Relevance
“…In 1999, Oka et al [4] classified tectal tumors into 3 groups based on MRI appearance, neuroendoscopic findings, histopathology, and postoperative clinical findings: group 1 - gliosis, group 2 - benign astrocytomas, and group 3 - anaplastic astrocytomas [4]. Today, it is well known that most tectal lesions are either hamartomas or pilocytic astrocytomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1999, Oka et al [4] classified tectal tumors into 3 groups based on MRI appearance, neuroendoscopic findings, histopathology, and postoperative clinical findings: group 1 - gliosis, group 2 - benign astrocytomas, and group 3 - anaplastic astrocytomas [4]. Today, it is well known that most tectal lesions are either hamartomas or pilocytic astrocytomas.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have demonstrated that only 20-30% of all lesions show interval growth on follow-up MRIs, requiring surgical resection at some point [2,3,4]. Thus, the management of most patients is conservative, treating the commonly present hydrocephalus with a ventriculoperitoneal shunt (VPS) or endoscopic third ventriculostomy (ETV), with long-term clinical follow-up using serial MRIs for changes in tumor signal or size [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these reports describe the use of endoscopes in minimally invasive approaches to the supraorbital region 11 or removal of tumors in difficult to access areas such as the pineal, 12 tectal, 13 sellar, 7 posterior fossa, [14][15][16] and intraventricular regions. [17][18][19] Studies in people have primarily focused on technique, safety, and efficacy of endoscopic assistance [20][21][22] ; there are no reports directly comparing outcomes between endoscopic-assisted procedures to similar procedures without use of the endoscope.…”
mentioning
confidence: 99%
“…Se ha descrito como una de las principales limitaciones de la neuroendoscopia el inadecuado control de las hemorragias cuantiosas 6 . Se postula que técnicas como la coagulación con láser podrían ayudar a solventar esta complicación 12,17 . Aún no se ha conseguido determinar si la diseminación leptomeníngea de algunas neoplasias puede estar favorecida por la técnica endoscópica o si es parte de la evolución natural de la enfermedad 2,16 .…”
Section: Discussionunclassified